2019
DOI: 10.3390/w11112248
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of Multiphase Extraction (MPE) Aiming at LNAPL Recovery in Tropical Soils

Abstract: Subsurface contamination by light non-aqueous phase liquids (LNAPL) is a widespread global problem that requires appropriate techniques to remediate soil and groundwater. In this paper, the subsurface transport over multiple phases (STOMP) model was used to simulate LNAPL multiphase flow and transport during multiphase extraction (MPE) application in two Brazilian tropical soils (silty sand and oxisol) contaminated by diesel. The model was applied to a hypothetical contamination site, with the initial LNAPL th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 28 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…152, 2006). In such complex settings, main challenges are either the capability to locate sources (Alberti et al, 2016a;Bortoni et al, 2019) and to track the plumes (Stefania et al, 2018;Colombo et al, 2019) or to define the DPBLs representative for the broad area to which the plumes overlap (Azzellino et al, 2019). Improving the capability of tracking plumes and the apportionment of contaminant sources will make remediation strategies more effective, allowing to identify the polluter, which should be charged with the liability costs for remediation (Alderuccio et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…152, 2006). In such complex settings, main challenges are either the capability to locate sources (Alberti et al, 2016a;Bortoni et al, 2019) and to track the plumes (Stefania et al, 2018;Colombo et al, 2019) or to define the DPBLs representative for the broad area to which the plumes overlap (Azzellino et al, 2019). Improving the capability of tracking plumes and the apportionment of contaminant sources will make remediation strategies more effective, allowing to identify the polluter, which should be charged with the liability costs for remediation (Alderuccio et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Diesel fuel with a mass density of 0.830 to 0.836 g cm −3 and viscosity at 3.45 × 10 −3 Pa s as well as convey relative permittivity value of 2.7 while relative permittivity of water was 80 with mass density of water was 1 g cm −3 with dynamic viscosity of water is 8.90 × 10 −4 Pa·s. 10,12,33,38 The high velocities estimated near the scattered diesel in sandbox experiment were highlighted by Bano et al 19 This explained at least partial pore water replacement by the diesel in lateral flow.…”
Section: Resultsmentioning
confidence: 93%
“…As the LNAPLs, diesel is diffused into the saturated zone by increase soil water repellence, flows through the vadose zone until it is trapped within the water table and impermeable layer that associated buoyancy forces arising. 10,33,34 Meanwhile, the strong amplitude of the waveform on GPR reflection in this zone resulted in the reduction of the electrical conductivity of the soil. It was found that the flow of saturated and dissolved water took place in the stratigraphic of Terap Red soil in slow horizontal motion, with a plumb placed at the centre of gravity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This aging or weathering can cause modifications that are necessary to consider when selecting a remediation technique and is therefore essential to the polluted siteʼs management (Lari et al 2019a ; Tang et al 2012 ). The light non-aqueous phase liquid (LNAPL) recovery and contamination mitigation approaches may include hydraulic pumping (mainly to recover the LNAPL), soil vapor extraction (SVE), chemical oxidants (e.g., to reduce saturation and degrade contaminants), air sparging (e.g., to augment biodegradation and volatilization), thermal methods (e.g., to decrease LNAPL viscosity and increase volatilization), enhanced bioremediation, multiphase extraction (MPE), skimming of mobile LNAPL, and natural source zone depletion (i.e., NSZD) (Besha et al 2018 ; Bortoni et al 2019 ; Gatsios et al 2018 ; Kuppusamy et al 2020 ; Lari et al 2019a ; Lari et al 2020 ; Ossai et al 2020 ; Sharma et al 2020 ; Verardo et al 2021 ; Xie et al 2020 ; Yao et al 2020 ). Among the physical extraction-based remediation techniques, the pump-and-treat is traditionally the most commonly used approach for treating contaminated groundwater (Brusseau 2019 ; Teramoto et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%